THE SUBSTANTIATION OF DEXMEDETOMIDINE USING IN VETERINARY PRACTICE FOR SMALL PETS’ SURGERIES - Omelyanenko , O. E. (Scientific Progress & Innovations, 2020)
Veterinary anesthesiology is a rather young science, and now searching optimum patterns and prepara- tions for using in surgeries of small pets is taking place. Most often 2 types of anesthesia are used – inhala- tion and intravenous. However, due to the high cost of the equipment for maintaining inhalation anesthesia, it is used intravenously more often. The study was conducted at the veterinary clinic “Na Robochiy” in the city of Dnipro. The purpose of the study was to determine the sedative and analgesic effect in comparison with the previous generations of the preparations mentioned below. During the research, 2 groups of dogs were formed, 5 animals in each, in the first (experimental) group anesthesia regimens were used applying Dexmedetomidine + Propofol + Butorphanol, in the second group (control) the pattern applying Sedazine + Propofol + Butorphanol was used. It turned out that the state of anesthesia was faster by 41.7 % in the ex- perimental group. The duration of anesthesia in the experimental group was by 33.3 % longer, which made it possible to conduct longer surgeries. Studying the effect on the organism systems it was revealed that the blood pressure in the experimental group after introducing the preparation was temporarily reduced, but it quickly increased to physiological rates, while in the control group its decrease was uncontrolled and re- quired correction. As for the analgesic effect, heart rate, arterial pressure (average), abdominal muscle con- traction during 4 surgical periods were investigated, (before the surgery, during the white line dissection, during the most traumatic interventions, and the state of recovery after anesthesia). It was found that in the experimental group, the heart rate (during all stages of the study) was kept within 100.8 beats/min, arterial pressure – within 100.6 mm of mercury, contractions of the abdominal wall muscles were not noticeable, while the indicators of the control group were the following: HR at different periods had different indicators (average 112.6 beats/min), arterial pressure was 110.3 mm of mercury, while the abdominal wall muscle contractions were quite noticeable. Concerning the analysis of analgesic effects, it can be said that while conducting more traumatic manipulations and in the state of recovery after anesthesia, the difference of in- dicators between the experimental and control groups was 24.1 % and 9.4 %. Analyzing all the presented data, it is possible to say that using the scheme Dexmedetomidine + Propofol + Butorphanol is more effec- tive concerning a faster entering analgesia, a longer period of anesthesia, and better indicators of animal analgesia.